Phytotoxicity indexes and removal of color, COD, phenols and ISA from pulp and paper mill wastewater post-treated by UV/H2O2 and photo-Fenton - Carvalho Neves, Ludmila; Beber de Souza, Jeanette; de Souza Vidal, Carlos Magno; Herbert, Lucila Thomsett; de Souza Vidal, Kely Viviane; Martins, Kely Geronazzo; Young, Brian Jonathan (Elsevier, 2022)
Pulp and paper mill wastewater (PPMWW) contains high concentrations of recalcitrant compounds that cause toxicity to organisms. Advanced oxidation processes (AOPs) have the ability to degrade these compounds and reduce overall toxicity. Physicochemical characterization and Lactuca sativa toxicity test were conducted to compare the effectiveness of two post-treatments: UV/H2O2 and photo-Fenton. A comparison of four phytotoxicity indexes was carried out. PPMWW from a Brazilian treatment plant was characterized by high values of phenols, color, integrated spectral area (ISA), and chemical oxygen demand (COD), and caused significant inhibition to seedling development. The use of both post-treatments allowed the removal of over 75% of phenols, color, ISA, and COD. Although UV/H2O2 was more effective in removing phenols and ISA, photo-Fenton better reduced phytotoxicity. The most sensitive phytotoxicity indexes were RGIC0.8 and GIC80%, whereas SGC0, REC-0.25 and REC-0.50 better showed the effectiveness of the post-treatments. We suggest the combined use of two phytotoxicity indexes: one that evaluates the effects on seed germination and, another, on root elongation, e.g., SGC0 and RGIC0.8. Additionally, we recommend the use of ISA for monitoring programs of wastewater treatments because it is a cost-effective approach that allows narrowing down the search and identification of compounds present in complex mixtures.